2020
DOI: 10.1161/strokeaha.120.029025
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Distal Embolization From tPA (Tissue-Type Plasminogen Activator) Administration Prior to Endovascular Stroke Treatment

Abstract: Background and Purpose: In large artery occlusion stroke, both intravenous (IV) tPA (tissue-type plasminogen activator) and endovascular stroke treatment (EST) are standard-of-care. It is unknown how often tPA causes distal embolization, in which a procedurally accessible large artery occlusion is converted to a more distal and potentially inaccessible occlusion. Methods: We analyzed data from a decentralized stroke telemedicine program in an integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Furthermore, a recent study covering 21 hospitals showed that DMVO occurred in one in four patients receiving intravenous tissue plasminogen activator in whom distal MT was not attempted in 41.3%, thereby depriving a significant number of patients of a possible better clinical outcome. 19 Intra-arterial thrombolysis may be achieved as an alternative to DMVO. 20 In the Bernese experience, the TICI rate was improved in 34% of patients treated by adjunctive intra-arterial Urokinase after incomplete or failed thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study covering 21 hospitals showed that DMVO occurred in one in four patients receiving intravenous tissue plasminogen activator in whom distal MT was not attempted in 41.3%, thereby depriving a significant number of patients of a possible better clinical outcome. 19 Intra-arterial thrombolysis may be achieved as an alternative to DMVO. 20 In the Bernese experience, the TICI rate was improved in 34% of patients treated by adjunctive intra-arterial Urokinase after incomplete or failed thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published RCT comparing endovascular thrombectomy with or without IVT in patients with LVO showed that MTE without prior IVT turned out to be non-inferior with regard to functional outcome, raising concerns that patients with LVO eligible for MTE are not adequately treated in a DS setting ( 3 ). There are even indications that IVT before MTE for LVO is associated with distal embolization, which in turn may reduce the chance that MTE can be attempted and recanalization can be achieved ( 16 ). But data on direct transfer of patients to CSC are still inconclusive as there are also trials which failed to prove non-inferiority of the MS model and proved its benefit prior ivtPA ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the strategies of ischemic stroke treatment currently available, the best therapeutic approach in the acute phase is thrombolysis with tPA; however, the therapeutic time window is extremely narrow (<4.5 h within stroke onset) (164). To expand the therapeutic window and, consequently, reach more patients with ischemic stroke, recent studies have focused on investigating immune cell-targeted therapies, such as anti-inflammatory drugs that are fundamentally non-invasive and effective approaches for ischemic stroke prevention (165).…”
Section: Anti-inflammatory Drugs Related To Monocytes and Macrophagesmentioning
confidence: 99%